Modeling and characterization of nano-gap contact acceleration switch for ultra-low power IoT sensor node - Hu, Zhongshi (Nanyang Technological University, 2023)
MEMS devices have been widely adopted in many areas of consumer electronics, automotive, and industrial applications due to their small size, low power consumption and low-cost integration. However, the always-on sensors based on MEMS have a standby power consumption. With the development of IoT, more commercialized sensors has been put into use, the standby power consumption has gradually become not negligible. This dissertation focuses on reducing the power consumption by realizing the sensing function with a conditionally triggered switch. The switch is fabricated as much closed as a non-capacitance device to minimize the power consumption in sleep mode. When external excitation exceeds the switch’s threshold, the switch will close , thus the monitoring of the specialized condition can be achieved. In this dissertation, we present MEMS acceleration switch. The switch can be conditionally triggered under external acceleration over its threshold. The threshold can be tuned by adjusting the air gap within the MEMS structure in fabrication process. New structures are also tested to achieve better performance. To evaluate the MEMS performance, prior simulations on both mechanical and electrical behavior were done to verify the structural design. Modification in circuit scheme level was made to minimize influence of the electrical problems such as current overshoot. FEM simulation was proceed to check the mechanical performance. The floating structure of the switch is fabricated by the new fabrication platform. After the simulation, practical measurements were done to verify the device performance and check the unsimulated problems when mechanical and electrical coupling was induced. The results are evaluated and give some potential applications based on the device performance. Furthermore, few approaches to reduce the unwanted issue in switch operation also tested.